Análisis contable de una combinación de negocios: la adquisición de Carrefour Colombia por CENCOSUD Chile (2014)
In 2012 the Chilean business group of the retails sector CENCOSUD acquired for about 2620 million dollars the Colombian subsidiary of the French brand Carrefour. The purpose of this paper is to present a brief conceptual analysis of this business combination process, under the International Financial Reporting Standard IFRS 3, issued by the IASB on March 2004, which applies to such transactions.